Personal cumulative factor as a basis of estimation of knowledge on professional pedagogics - Vasiliev, I. B.; Bakatanova, V. B. (Problems of Engineer-Pedagogical Education, 2018)
In due time the new author’s course «Professional pedagogic» has been entered into the maintenance of pedagogical preparation of students of engineering-pedagogical specialties. Creation of technology of its studying has demanded working out of some methodical approaches. In article it is defined that application of personal cumulative factor (PCF) was one of such approaches. It has allowed making an estimation of mastering of a course integrated (result-flowing) and students’ work regular. Thus in practice the didactic principle of a system of training has been realized. Results of application PCF in Ukrainian Engineering-Pedagogical Academy testify that in experimental groups absolute progress has raised on 18,5 %, and qualitative – on 24 %. The subsequent check of this approach in Kazakhstan (Almaty Humanitarian-Technical University, Kazakh National Agrarian University) also has allowed to ascertain increase of the academic progress: absolute – on 21,7 %; qualitative – on 28,6 %. The analysis of prospects of the further researches testifies that ПКК can be applied at studying of any training course where it is used testing and traditional forms of control of knowledge.